A potential role for T-type calcium channels in homocysteinemia-induced peripheral neuropathy - Gaifullina, Aisylu S; Lazniewska, Joanna; Gerasimova, Elena V; Burkhanova, Gulshat F; Rzhepetskyy, Yuriy; Tomin, Andriy; Rivas-Ramirez, Paula; Huang, Junting; Cmarko, Leos; Zamponi, Gerald W; Sitdikova, Guzel F; Weiss, Norbert (Pain, 2019)
Homocysteinemia is a metabolic condition characterized by abnormally high level of homocysteine in the blood and is considered to be a risk factor for peripheral neuropathy. However, the cellular mechanisms underlying toxic effects of homocysteine on the processing of peripheral nociception have not yet been investigated comprehensively. Here, using a rodent model of experimental homocysteinemia, we report the causal association between homocysteine and the development of mechanical allodynia. Homocysteinemia-induced mechanical allodynia was reversed on pharmacological inhibition of T-type calcium channels. In addition, our in vitro studies indicate that homocysteine enhances recombinant T-type calcium currents by promoting the recycling of Cav3.2 channels back to the plasma membrane through a protein kinase C-dependent signaling pathway that requires the direct phosphorylation of Cav3.2 at specific loci. Altogether, these results reveal an unrecognized signaling pathway that modulates the expression of T-type calcium channels, and may potentially contribute to the development of peripheral neuropathy associated with homocysteinemia.
Keywords: Disease Models, Animal; Calcium; Animals; spinální ganglia; hyperalgezie; Hyperalgesia; Hyperhomocysteinemia; Rats, Wistar; Cell Membrane; Rats; nemoci periferního nervového systému; Ganglia, Spinal; modely nemocí na zvířatech; Calcium Channels, T-Type; hyperhomocysteinemie; Peripheral Nervous System Diseases; vápníkové kanály - typ T; zvířata; Homocysteine; homocystein; nocicepce; vápník; buněčná membrána; potkani Wistar; krysa rodu Rattus; Nociception